Analisis Jenis Kalimat Langsung pada Teks Opini Bertema Pendidikan bagi Perempuan di Website ‘IDN Times’ Edisi April 2024 sebagai Sumber Edukasi - Helga Tsania Rahma Putri; Meca Chelsillia Ayunindar Putri; Herlina Novita Sari; Siti Anisa Priyanti; Syafina Izzatun Yazidahayu; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Amilia Buana Dewi Islamy (BADAN PENERBIT STIEPARI PRESS, 2025)
Study aims to identify and analyze the types of direct sentences in opinion texts on women's education published on the IDN Times website in the April 2024 edition. This research uses a descriptive qualitative approach with a literature study method, which is also supported by simple quantitative data analysis to determine the proportion of each type of direct sentence. The analysis results show that of the eleven direct sentences found, the majority are statements of fact, followed by statements of opinion and invitations or appeals. This finding indicates that opinion-text writers prioritize concrete data and facts to strengthen their arguments. However, opinion and invitation elements are still present as rhetorical elements that enrich the narrative and enhance persuasion efforts toward readers. Therefore, using direct sentences in opinion texts proves effective in conveying social issues and building public understanding, especially regarding the importance of education for women.